2006
DOI: 10.1111/j.1440-1614.2006.01761.x
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder attitudes and psychopathology in Caucasian Australian, Asian Australian and Thai university students

Abstract: Eating disorder attitudes and psychopathology scores in the Thai group were found to be highest. The Asian Australian group did not have significantly higher scores on the EAT-26 than the Caucasian Australian group, but had higher scores in some subscales of the EDI-2. That the Thai group had the highest scores in susceptibility to developing an eating disorder and eating disorder psychopathology may be partially explained in sociocultural terms, with pressure to be thin more extreme in Thailand than in Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…12 Finally, there was no need for translation of study measures in the present study, as in most other studies of eating-disordered behavior in Asian populations. 3,5,6,12 These considerations notwithstanding, it will be important to include appropriate measures of clinical significance in future research of this kind. Further investigation of the psychometric properties of the EDE-Q in the Singaporean population would also be of interest.…”
Section: Study Limitations and Other Methodological Considerationsmentioning
confidence: 98%
See 1 more Smart Citation
“…12 Finally, there was no need for translation of study measures in the present study, as in most other studies of eating-disordered behavior in Asian populations. 3,5,6,12 These considerations notwithstanding, it will be important to include appropriate measures of clinical significance in future research of this kind. Further investigation of the psychometric properties of the EDE-Q in the Singaporean population would also be of interest.…”
Section: Study Limitations and Other Methodological Considerationsmentioning
confidence: 98%
“…18,19 In those few community-based studies of eatingdisordered behavior conducted in south-east Asia, the assessment has been confined, almost entirely, to reports of mean scores on subscales of the Eating Attitudes Test (EAT) or Eating Disorders Inventory (EDI), along with the proportion of participants scoring above the suggested EAT cut-off for a probable eating disorder. [3][4][5][6][20][21][22] As suggested earlier, these studies have found that levels of body dissatisfaction and overall eating disorder psychopathology in newly industrialized Asian countries are as high as, if not higher than, those observed in Western nations. More specific information, however, is lacking.…”
Section: Introductionmentioning
confidence: 97%
“…The western concept of beauty and attractiveness in thinness is diffusing among the youth of some nonwestern countries like Philippines [57] and Thailand [58]. Lorenzo et al [59] found in his study that disordered eating attitude and behaviour among adolescents are becoming a significant problem in Philippines.…”
Section: Situation In Nonwestern Countriesmentioning
confidence: 99%
“…However, the prevalence of eating disorders in adolescents is reported to be increasing with time so these results must be interpreted with caution. Significantly higher scores on all three EDI‐3 eating disorder risk scales were also seen compared to Australian women aged 18–22 years …”
Section: Discussionmentioning
confidence: 89%